Sex‐Specific Association of Obstructive Sleep Apnea With Retinal Microvascular Signs: The Multi‐Ethnic Study of Atherosclerosis. Issue 7 (July 2016) - Lin, Gen‐Min; Redline, Susan; Klein, Ronald; Colangelo, Laura A.; Cotch, Mary Frances; Wong, Tien Y.; Klein, Barbara E. K.; Patel, Sanjay R.; Shea, Steven J.; Liu, Kiang
Abstract : Background: Obstructive sleep apnea (OSA) is a common condition affecting more men than women. The relationship of OSA with microvascular disease is unclear, complicated by possible sex difference. Assessment of the relationship of OSA with retinal microvascular signs in men and women may provide insights into such a relationship. Methods and Results: We examined the sex‐specific cross‐sectional association of OSA severity with retinal vascular calibers in 1808 participants, and with specific retinopathy signs in 1831 participants from a sample of 2060 participants aged 54 to 93 years who underwent successful polysomnography in the Multi‐Ethnic Study of Atherosclerosis, 2010–2012. OSA severity was defined by the apnea–hypopnea index (events/h) as none (<5), mild (5–14.9), moderate (15–29.9), and severe (≥30). As compared to no OSA, moderate/severe OSA in men was associated with retinal arteriolar narrowing (odds ratio [OR] and 95% CI for the narrowest quartile: 1.65 [1.00–2.71]) and retinal venular widening (1.80 [1.07–3.04] for the widest quartile), but not in women (odds ratio: 1.10 [0.67–1.81] and 0.91 [0.58–1.43], respectively) after adjusting for age, race/ethnicity, body mass index, pack‐years of cigarette smoking, alcohol intake, hypertension duration, diabetes mellitus duration, HbA1c levels, lipid profile, micro‐/macroalbuminuria, estimated glomerular filtration rate, β‐blockers use, antihypertensive therapy, and lipid‐lowering therapy. In contrast, severe OSA was associated with retinal microaneurysms in women, but not in men (odds ratio: 3.22 [1.16–8.97] and 0.59 [0.27–1.30], respectively). Conclusions: The associations of OSA severity with retinal microvascular signs may differ by sex. Whether these findings were related to sex differences in OSA exposure needs further investigation.